Euro area sovereign debt crisis and debt mutualisation - Afonso, António (2016)
We study debt mutualisation in the Euro area. Bearing in mind other existing proposals we provide an alternative Blue, Yellow and Red Bonds proposal: blue, would cover debt up to 60% of GDP, yellow would include debt from 60% up to 90% of GDP, and red would cover debt above 90% of GDP. Although not with joint liability, the rationale behind the Yellow Bonds with a joint issuance is the attraction of liquidity, which would be beneficial, especially for the countries with high yields. This could give more room to public authorities.